(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
Among medieval institutions, the development of monasticism represents one of the main innovations, both in the east as well as in the west, that marked the formation of european civilization. It was originated as a spontaneous movement within Christianity, it developed over the centuries responding to the social needs of spiritual and religious renewal; a process occurred in accordance with the canonical norms indicated by the Church authorities. The influence of the Regula Benedicti in particular, and together with it the progressive disciplinary orientation of the papacy, estalished a fundamental turning point and this direction, starting from the eighth century, was not only assumed by the Carolingian reform of the synods of Aachen, but became the reference of any subsequent cloistered reform of european monasticism.